2020
DOI: 10.1186/s12913-020-4928-x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation status of household contact tuberculosis screening by health extension workers: assessment findings from programme implementation in Tigray region, northern Ethiopia

Abstract: Background: In the Tigray region of Ethiopia, Health Extension Workers (HEWs) conduct Tuberculosis (TB) screening for all household (HH) contacts. However, there is limited evidence on implementation status of HH contact TB screening by HEWs. The aim of this program assessment was to describe the implementation status and associated factors of HH contact TB screening by HEWs. Methods: This programme assessment was conducted in three randomly selected districts from March to April 2018. Data was collected by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…This could be due to the active involvement of community members mainly WDA leaders in presumptive TB identification. This finding is supported by the previous studies done in Ethiopia which revealed that HEWs who discussed TB issues through regular meeting with WDA leaders had a role in improving TB screening practice [19]. In Ethiopia, the WDA leaders are primary contact with communities and they are expected to search for people with symptoms of TB in their team by asking whether anyone in the households have had a cough for two weeks or more and then they inform to HEWs immediately if there are symptomatic TB individuals [13].…”
Section: Plos Onesupporting
confidence: 83%
See 2 more Smart Citations
“…This could be due to the active involvement of community members mainly WDA leaders in presumptive TB identification. This finding is supported by the previous studies done in Ethiopia which revealed that HEWs who discussed TB issues through regular meeting with WDA leaders had a role in improving TB screening practice [19]. In Ethiopia, the WDA leaders are primary contact with communities and they are expected to search for people with symptoms of TB in their team by asking whether anyone in the households have had a cough for two weeks or more and then they inform to HEWs immediately if there are symptomatic TB individuals [13].…”
Section: Plos Onesupporting
confidence: 83%
“…Furthermore, WDAs supports HEWs in liaising them with community members. HEWs have been conducting regular meetings with the WDA leaders, exchanging feedback on their work and receiving reports of activities performed by the WDA leaders [ 19 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another study in Tigray reported a low level of knowledge about the cause of TB and the consequences of a poor treatment adherence to its treatment [ 69 ]. Besides, a recent assessment report in Tigray Region indicates that only 21.7% of household contacts were screened for TB by health extension workers [ 70 ], which are by far lower than the target stated by the national TB program to screen all household contacts [ 71 ] and WHO target of greater than 90% household contacts to be screened for TB [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health education regarding TB by health care workers is a factor that improves screening adherence of household contact by 2.6 times (Shiferaw et al, 2019). Other studies revealed that health education by health extension workers to household contact was an important factor in improving their participation in TB screening by 4.2 times (Gebretnsae et al, 2020).…”
Section: Discussionmentioning
confidence: 99%